2022
DOI: 10.1128/spectrum.00470-22
|View full text |Cite
|
Sign up to set email alerts
|

No Genus-Specific Gene Is Essential for the Replication of Fowl Adenovirus 4 in Chicken LMH Cells

Abstract: Identification of viral essential genes is important for adenoviral vector construction. Deletion of nonessential genes enlarges cloning capacity, deletion of essential genes makes a replication-defective vector, and expression of essential genes in trans generates a virus packaging cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The strong activity of the 37,061-nt promoter had been revealed by expressing reporter genes in our previous work [ 48 ]. This promoter mainly produced transcripts for GAM1, ORF19A-e865aa and ORF19A-t336aa ( Figure 7 and Figure S11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong activity of the 37,061-nt promoter had been revealed by expressing reporter genes in our previous work [ 48 ]. This promoter mainly produced transcripts for GAM1, ORF19A-e865aa and ORF19A-t336aa ( Figure 7 and Figure S11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wet-lab experiments provided evidence to support the PCR-cDNA results. In a previous study, we found two regions in the FAdV-4 genome that possessed promoter activity [ 48 ]. By determining the expression of reporter genes, we quantified their strength.…”
Section: Discussionmentioning
confidence: 99%
“…The genome of FAdV is about 8–10 kb longer than that of HAdV. The regions encoding genus-specific genes are approximately 7 kb on the left and 10 kb on the right in FAdV-4 genome, and no genus-specific gene is essential for the virus replication [ 20 ]. In F2CF1K-CG or FAdV4-CG, about 4.7 kb of virus genome has already been deleted.…”
Section: Discussionmentioning
confidence: 99%
“…HAdV41-CG originated from human adenovirus 41, and the E1 and E3 regions in the genome were deleted and replaced with CMV promoter (CMVp) controlled GFP expression cassette and HAdV-5 ADP gene, respectively [ 26 ]. pKFAV4S-GFP is an adenovirus plasmid, and it carries deletions of ORF0, ORF1, ORF1B, ORF2 and ORF19A in FAdV-4 genome; and at the left deletion site in the genome, a CMVp controlled GFP expression cassette was inserted, which was flanked with two SwaI sites to facilitate transgene replacement [ 20 ]. pMD-FAV4Fs is an intermediate plasmid for FAdV-4 fiber modification, which contains fiber1 and fiber2 genes of FAdV-4 [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation